Evaluasi Pembelajaran Daring Melalui Media Whatsapp Di Era Pandemi (Studi Kasus Di MI Muhammadiyah Purworejo) - Siti Muliyanti; Abuzar Al Ghifari; Taufiq Nur Azis (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2023)
Online learning is a learning activity that utilizes today's technology by using the internet as a bridge to replace ordinary learning during the ongoing pandemic. The online learning method itself does not require students to be present in class, students can access the learning through internet media. The purpose of this study is to evaluate the extent to which the use of WhatsApp learning media is effective and can be used. The method used is a qualitative method, data collection techniques using observation, interviews, and documentation through teachers, parents, and students. The results of the research are: (1) the use of WhatsApp media is not yet effective and implemented optimally, (2) The percentage of the relationship between teachers, students, and parents in the use of WhatsApp media is still not directed, (3) the evaluation of online learning is not optimal.